2018
DOI: 10.4310/joc.2018.v9.n3.a7
|View full text |Cite
|
Sign up to set email alerts
|

Not all simple looking degree sequence problems are easy

Abstract: Degree sequence (DS) problems are around for at least hundred twenty years, and with the advent of network science, more and more complicated, structured DS problems were invented. Interestingly enough all those problems so far are computationally easy. It is clear, however, that we will find soon computationally hard DS problems. In this paper we want to find such hard DS problems with relatively simple definition.For a vertex v in the simple graph G denote d i (v) the number of vertices at distance exactly i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This motivated the question: "What kind of local properties make the graph construction hard?" Erdős and Miklós showed that it is already NP-complete to ask if there exists a graph with given degree and neighbor degree sequence [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This motivated the question: "What kind of local properties make the graph construction hard?" Erdős and Miklós showed that it is already NP-complete to ask if there exists a graph with given degree and neighbor degree sequence [7].…”
Section: Introductionmentioning
confidence: 99%
“…is the degree of vertex v and N (v) is the set of the neighbors of v? Erdős and Miklós showed that this decision problem is NP-complete in general [7]. Here we consider a specific case: the maximum degree is 4, and we are looking for connected realizations.…”
Section: Introductionmentioning
confidence: 99%